CULTURAL AND PRAGMATIC DETERMINANTS OF TRANSLATION STRATEGIES IN UZBEK-ENGLISH INTERCULTURAL COMMUNICATION - Mukhammadieva Umida (International Journal of Literature and Language Studies, 2026)
This article examines the pragmatic and cultural determinants that shape translation strategies in Uzbek-English intercultural communication. In the context of globalization, translation is no longer viewed solely as a process of linguistic substitution; rather, it functions as a complex intercultural mediation in which semantic transfer is closely connected with pragmatic intention, sociocultural norms, and discourse conventions. The study applies comparative-linguistic, pragmatic, discourse-functional, and intercultural approaches to identify the key factors influencing translation decisions between Uzbek and English. The analysis demonstrates that politeness systems, hierarchical relations, indirectness, culturally marked lexical units, metaphorical structures, and genre-specific rhetorical organization significantly affect translation adequacy. The article argues that formal equivalence alone is insufficient for achieving communicative success in intercultural contexts and that functional-pragmatic equivalence should be prioritized. Special attention is given to examples from literary, academic, publicistic, and official discourse in order to illustrate how translation transformations operate in practice. On the basis of the findings, a systematic model of translation strategies is proposed, including pragmatic substitution, structural reorganization, descriptive expansion, selective retention, and contextual neutralization. The results may be applied in translator training, academic research, and professional translation practice in the Uzbek-English language pair.